The importance of multimodal play and storytelling in medtech for children: A Case Study of Co-designing a Mixed Realities Play Kit to Prepare 4 to 10-year-Olds for an MRI Scan. Issue 2 (June 2023) - Yamada-Rice, Dylan; Love, Steve; Thompson, Jill; Thompson, Sean; McQuillian, Helen
This article examines the research and development of a mixed realities play-kit to prepare children for an MRI scan to be undertaken without the need for a General Anaesthetic. The kit uses three different types of play; augmented, virtual reality and physical to help children become familiar with the look of an MRI scanner, the noises it makes, the role of the radiographer, what to expect when they go to hospital and to practise staying still. We reflect on the initial multimodal research methods that were used to bring children into the first stages of the design and development process. These included, model making, drawing, play and informal conversations. From which, data were analysed with visual and thematic means to make an original contribution to the field of medtech design for children, in that we found young children (aged six and under) prefer to receive medical information through opportunities for multimodal play and storytelling. As a direct result of this finding, we matched different play types to the various areas of preparation outlined above. In doing so, paying attention to the specific affordances of the different ways in which modes are combined depending on if physical, augmented or virtual reality play are used. Such findings are likely to be useful to other researchers and developers creating medtech products for young children. For those interested in multimodality specifically, this article also provides insight into the connection between information, modes of communication and play and the application of these to research design.